1992
DOI: 10.1177/0164027592144002
|View full text |Cite
|
Sign up to set email alerts
|

The Existence and Emotional Closeness of Relationships with Children, Friends, and Spouses

Abstract: Based on a social support model, the authors analyzed the association between the experience of loneliness and the emotional closeness older persons have in their social relationships with their children, friends, and spouses. The effects on loneliness of age, sex, subjective health status, economic situation, need for attachment, and need for social integration were also examined and controlled. Results are based on 1,071 participants in the congregate and home-delivered meal programs of the Senior Citizens N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…Older people who maintained contacts with friends and were satisfied with these relationships expressed lower feelings of loneliness (Mullins, Smith, Colquitt, & Mushel, 1996). A positive relationship was found between having friends and life satisfaction and morale among elderly people (Mancini, 1980; Mullins & Mushel, 1992; Strain & Chappell, 1982). Creecy and Wright (1979) found that a greater frequency of activity with friends was positively related to morale among European American but not among African American elderly persons.…”
Section: Social Support Network and Lonelinessmentioning
confidence: 99%
“…Older people who maintained contacts with friends and were satisfied with these relationships expressed lower feelings of loneliness (Mullins, Smith, Colquitt, & Mushel, 1996). A positive relationship was found between having friends and life satisfaction and morale among elderly people (Mancini, 1980; Mullins & Mushel, 1992; Strain & Chappell, 1982). Creecy and Wright (1979) found that a greater frequency of activity with friends was positively related to morale among European American but not among African American elderly persons.…”
Section: Social Support Network and Lonelinessmentioning
confidence: 99%
“…Research has shown that friends, especially close friends, exert a positive influence on the emotional well-being of older persons (Crohan & Antonucci, 1989;Mullins & Mushel, 1992). Besides serving as confidants, they provide numerous forms of social and emotional support, which are valued and appreciated, many times because the support is nonobligatory.…”
Section: Age and Gendermentioning
confidence: 99%
“…Dykstra et al indicated that with age the chance that someone will outlive their partner and lose age‐matched friends increases . Another study found that changes in the social network of older adults predict loneliness . Furthermore, loneliness increases among older adults when aging; above 55 years of age, older persons tend to be lonelier than younger persons .…”
Section: Introductionmentioning
confidence: 98%